Casual Associations and Shape Between Prepuberty Body Mass Index and Early Onset of Puberty: A Mendelian Randomization and Dose–Response Relationship Analysis - Fang, Jiao; Yuan, Jingyi; Zhang, Dandan; Liu, Wanxu; Su, Puyu; Wan, Yuhui; Zhang, Zhihua; Tao, Fangbiao; Sun, Ying (Frontiers in Endocrinology, 2022)
Background There is an ongoing controversial issue regarding whether onset of puberty is related to childhood BMI. Objectives This study aims at investigating the causal association and its shape between prepuberty BMI and early puberty onset. Methods Breast development and testicular volume were assessed annually from a population-based prospective cohort of 997 children for consecutive years by professional endocrinologists. Seventeen puberty- and BMI-related SNPs were selected to calculate the polygenic risk score. The two-stage least square method was used to assess and confirm causal effects. A dose–response association between prepuberty BMI and early puberty onset was conducted by using restricted cubic spline Cox regression. Results After adjusting for covariates, prepuberty BMI was positively associated with early thelarche among girls (coefficients = 0.18, 95% CI: 0.01, 0.29). A non-linear model suggested an inverted U-shaped relationship between prepuberty BMI and risk for early thelarche (χ2 = 276.3, p < 0.001). The risk for early thelarche increased rapidly from prepuberty BMI at 15.70 kg/m2 (P25) to 20.75 kg/m2 (P85) and gradually decreased afterward. Compared with the P25 of prepuberty BMI, the HRs (95% CI) for early thelarche were 5.08 (1.15, 8.55), 4.48 (1.02, 7.74), 10.15 (3.93, 17.50), and 8.43 (1.91, 13.71) for percentiles P25–P50, P50–P75, P75–P85, and ≥P85 of BMI categories, respectively. In boys, compared with the P25 of prepuberty BMI, boys with BMI between P25 and P50 showed an increased risk of early puberty (HR: 3.94, 95% CI: 1.44, 6.80). Conclusions Prepuberty BMI may serve the purpose of identifying the girls at higher risk of early thelarche, which could assist in the adaptation of prevention and intervention strategies targeting childhood obesity. The findings emphasize a non-linear correlation between prepuberty BMI and early puberty onset.